2010
DOI: 10.1007/s10658-010-9631-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Apple stem grooving virus causing leaf distortion on pear (Pyrus pyrifolia) in Taiwan

Abstract: A putative virus-induced disease of pear (Pyrus pyrifolia var. Hengshen) showing symptoms of reduced size of foliage and leaf distortion was observed in orchards in central Taiwan in 2004. The sap of symptomatic leaf samples reacted positively to an antiserum against Apple stem grooving virus (ASGV). Two virus cultures, designated as TS1 and TS2, were isolated from symptomatic pears. Flexuous filamentous virions of similar to 12 x 600 nm were observed in symptomatic pear leaves and purified virus preparations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The ASPV proteins have the typical features of potex-like proteins (Jelkmann, 1994). Previous studies have revealed the remarkable genetic variability among ASPV isolates (Liu et al, 2012;Wu et al, 2010;Yeon et al, 2014).…”
mentioning
confidence: 99%
“…The ASPV proteins have the typical features of potex-like proteins (Jelkmann, 1994). Previous studies have revealed the remarkable genetic variability among ASPV isolates (Liu et al, 2012;Wu et al, 2010;Yeon et al, 2014).…”
mentioning
confidence: 99%
“…Recently, a pear plant showing symptoms of small leaves and leaf distortion in Taiwan has been identified to be caused by a pear isolate of ASGV (Wu et al, 2010). Another pear disease, consisting of chlorotic spots on the leaves of the pear cultivar Hengshen, had been observed in the orchards in central Taiwan.…”
mentioning
confidence: 99%
“…Their main means of transmission is through infected propagation plant material. Single infections with ASPV and ASGV are symptomless in apple but can cause diverse symptoms in pear like vein yellowing or red mottling, and pear black necrotic leaf spot, respectively (Pleše et al, 1975;Shim et al, 2004;Wu et al, 2010;Massart et al, 2011;). In addition, mixed infections of the three viruses are very common and can cause complex disease symptoms in both apple and pear trees, resulting in significant reduction in quality and yield (Posnette 1989;Petrzik and Lenz, 2002;Boulila 2010;Hadidi et al, 2011;Massart et al, 2011;.…”
Section: Introductionmentioning
confidence: 99%